PROPERTY PRODUCT PURCHASE DECISION ANALYSIS WITH DIGITAL MARKETING AND BRAND TRUST APPROACH - R. Fatia Aisyah Nanda Taufik; Hendra Galuh Febrianto (Universitas Muhammadiyah Tangerang, 2022)
AbstractThe purpose of this study was to determine the effect of digital marketing and brand trust on purchasing decisions for property products at PT. Kencana Berkat Propertindo either partially or simultaneously. The method used in this research is quantitative associative and the sampling technique uses non-probability sampling with a population of 204 consumers and a sample of 68 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, coefficient of determination test and hypothesis testing. The results of this study are Digital marketing has a significant effect on purchasing decisions with a sig.t value of 0.038 <0.5. Brand trust has a significant effect on purchasing decisions with a sig.t value of 0.004 < 0.5. Then sig. F of 0.000 <0.05 so it can be concluded that simultaneously digital marketing and brand trust variables have a significant effect on purchasing decisions at PT. Kencana Berkat Propertindo.Keywords: Digital Marketing, Brand Trust, Purchase Decision.